2008
DOI: 10.3949/ccjm.75.suppl_1.s10
|View full text |Cite
|
Sign up to set email alerts
|

Overview of breast cancer staging and surgical treatment options.

Abstract: Following diagnosis of breast cancer, patients undergo assessment for local and systemic treatment. Establishing a relationship and communication with the patient is critical to this assessment, as are history-taking, clinical breast examination, review of imaging studies, and interactive discussion with the patient of treatment options and possible breast reconstruction. Some type of surgical therapy is indicated in virtually all women with breast cancer, generally as the first part of a multicomponent treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2009
2009
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 9 publications
0
13
0
3
Order By: Relevance
“…11,21,23,24,25 Negative margin is assurance that the tumor burden is reduced to microscopic levels that can be controlled by radiation therapy whereas positive margins generally require a return to the operating room for further resection and clearance. 26 Limitations in tumor localization may lead to a greater incidence of positive resection. Recht et al 5 found a 67 per cent to 69 per cent reexcision rate in patients who underwent breast-conservation therapy between 1984 and 1992.…”
Section: Discussionmentioning
confidence: 99%
“…11,21,23,24,25 Negative margin is assurance that the tumor burden is reduced to microscopic levels that can be controlled by radiation therapy whereas positive margins generally require a return to the operating room for further resection and clearance. 26 Limitations in tumor localization may lead to a greater incidence of positive resection. Recht et al 5 found a 67 per cent to 69 per cent reexcision rate in patients who underwent breast-conservation therapy between 1984 and 1992.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a molecularly, pathologically, and epidemiologically heterogeneous disease. Clinically, invasive breast cancers can be classified into three groups: early breast cancer (stages I, IIa, and IIb), locally advanced breast cancer (stages IIIa, IIIb, and IIIc), and advanced breast cancer (stage IV) presenting with distant metastases beyond the regional lymph nodes (6,7).…”
Section: Clinical Charactermentioning
confidence: 99%
“…The dimensions of these layers are given in Table 1. In order to investigate early stage cancer, the tumor diameter has been kept under 20 mm [16]. …”
Section: Numerical Modelingmentioning
confidence: 99%